1997
DOI: 10.1128/jvi.71.7.5133-5139.1997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the differential subcellular localization of the 38- and 39-kilodalton structural proteins of Borna disease virus

Abstract: Borna disease virus (BDV) is a nonsegmented negative-strand (NNS) RNA virus that is unusual because it replicates in the nucleus. The most abundant viral protein in infected cells is a 38/39-kDa doublet that is presumed to represent the nucleocapsid. Infectious particles also contain high levels of this protein, accounting for at least 50% of the viral proteins. The two forms of the protein differ by an additional 13 amino acids that are present at the amino terminus of the 39-kDa form and missing from the 38-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Of some significance is the presence of two forms of the N protein that are essentially identical except for the presence of an amino-terminal 13-amino-acid extension containing an NLS. However, the BDV N protein derivative lacking the amino-terminal extension sequence is still able to localize to the nucleus, albeit less efficiently (35). Therefore, it appears that multiple NLSs are present in nucleocapsid proteins of several negative-strand viruses that replicate in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Of some significance is the presence of two forms of the N protein that are essentially identical except for the presence of an amino-terminal 13-amino-acid extension containing an NLS. However, the BDV N protein derivative lacking the amino-terminal extension sequence is still able to localize to the nucleus, albeit less efficiently (35). Therefore, it appears that multiple NLSs are present in nucleocapsid proteins of several negative-strand viruses that replicate in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the indirect immunofluorescent antibody assay (IFA) is commonly used for the detection of BDV antigens in infected cells (30,33). The IFA method is employed for determination of the viral titers as focusforming units (FFU) or 50% tissue culture infectious dose (TCID,).…”
mentioning
confidence: 99%
“…The intracellular localization of BoDV ribonucleoproteins (RNPs) is regulated by viral proteins containing NLSs and NESs as well as their interactions. N, P, X, and L harbor NLSs, and N and P contain NESs (11)(12)(13)(14)(15)(16)(17)(18). Previous studies have demonstrated that the interaction of accessory protein X with P enhances the nuclear export of P (19).…”
mentioning
confidence: 99%
“…In contrast, P directly binds to N, leading to the retention of N in the nucleus (13,20). N transcripts encode two isoforms, namely, full-length isoform N (p40) and N-terminally truncated isoform N= (p38), which is translated from the second initiation codon downstream of the NLS (17). While N mainly localizes to the nucleus, the solo expression of N= is found in the cytoplasm (12,13,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation